Sudden cardiac death: A comparative review of humans, dogs and cats. (August 2021) - Brugada-Terradellas, Celine; Hellemans, Arnaut; Brugada, Pedro; Smets, Pascale
Highlights: Sudden cardiac death results from multiple structural or electrical heart diseases. Few genetic mutations in animals are known to cause possible sudden cardiac death. Prevalence data for sudden cardiac death in animals is very scarce. Animals and humans could inform mutually beneficial research. Abstract: Sudden death is one of the most common causes of death in humans in Western countries. Approximately 85% of these cases are of cardiac origin. In dogs and cats, sudden cardiac death (SCD) also commonly occurs, but fewer pathophysiological and prevalence data are available. Both structural, primarily 'electrical' and ischemic heart diseases are known to cause SCD, many of which share similar underlying arrhythmogenic mechanisms between humans and companion animals. As for underlying genetics, numerous mutations on multiple loci have been related to SCD in humans, but only a few mutations associated with dilated cardiomyopathy and SCD have been identified in dogs, e.g. in the phospholamban and titin genes. Information published from human medicine can therefore inform future veterinary studies, but also dogs and cats could act as spontaneous models of SCD in humans. Further research in both fields is therefore warranted to better understand the pathophysiology, genetics, and prevention of SCD.